Perlindungan Hukum bagi Anak Usia Sekolah Terkait dengan Penyediaan Alat Kontrasepsi - Musfianawati, Musfianawati; Eka Adhining Tyas, Wahyu; Nazza Fauzi, Firda (Fakultas Hukum Universitas Islam Jember, 2025)
Article 103 paragraph 4 in PP No. 28 of 2024 concerning Health states the Provision of contraceptives for school-age children. The provision of contraceptives for school-age children is contrary to the principle of legal protection for children. Legal issues in this study: 1) Is the Provision of Contraceptives for School-Age Children Not Contrary to the Principle of Legal Protection for Children; 2) What is the Ratio Legis of the Regulations on the Article on the Provision of Contraceptives for School-Age Children in PP No. 48 of 2024 concerning Health. The purpose of this study is to determine and analyze the ratio legis and the regulation of the Provision of Contraceptives for School-Age Children Not Contrary to the Principle of Legal Protection for Children. This type of research is normative juridical. The results of the study are the ratio legis of PP No. 28 of 2024 concerning Health is to increase understanding and access for school-age and adolescents to reproductive health. Meanwhile, no additional explanation was found in Article 103 paragraph 4 point e regarding the provisions for the provision of contraceptives. If the focus is on those who are married, this is not in accordance with the category of the school age range that is allowed to marry. Meanwhile, if the focus is on education, it is less appropriate because the concept of provision means providing